New high-yielding sugarcane varieties for north-west zone - Chaudhary, Divya; Jeena, Anand Singh (Indian Farming, 2023)
Sugarcane is the primary source of sugar in India and serves as the main cash crop. It is cultivated in both tropical and sub-tropical regions across the country. The Northwest zone, which includes areas in Haryana, Punjab, Rajasthan, Uttarakhand plains, and western to central UP, is particularly notable for its sugarcane production. The key to enhancing the productivity and overall production of sugarcane lies in the adoption of new varieties and the replacement of seeds. In this context, various newly developed sugarcane varieties are good replacements for wonder cane Co 238, which has become susceptible to red rot disease. These sugarcane varieties are typically categorized into two groups based on their maturation period: early and mid-late. Their classification is dependent on their ability to attain 16% sucrose and 85% purity at either the 10-month or 12-month stage. Consequently, farmers are keen to know about new varieties for cultivation; hence, information on the characteristic features of these varieties is vital for popularizing these varieties.